The Influence of Relativism Ethics and Professional Commitment on the Intention to Conduct External Whistleblowing - Marini Purwanto (CONTABILITA : Journal of Accounting and Finance, 2025)
Whistleblowing considered as an effective method in preventing fraud. Whistleblowing actions, especially that occur externally, still face many challenges and are not easy to do. It’s require a lot of deliberation, dilemmas and possibility of higher risk in the process. So encouragement is required to be the factor to perform it. Some factors that can influence external whistleblowing are ethical relativism and professional commitment. This study aims to determine whether there is a difference between relativism ethics views and absolutism ethics views towards intention to perform external whistleblowing and to determine whether there is a difference between a high professional commitment and low professional commitment towards intention to perform external whistleblowing. This study uses a 2x2 experimental design and students of Widya Mandala Catholic University, Accounting S-1 majored as participants, the data test is carried out through two stages of testing, namely homogeneity test using Levene test and univariate ANOVA test to test the hypothesis. The results of the study show that there is a difference between relativism ethics views and absolutism ethics views towards intention to perform external whistleblowing. Where participants with ethical relativism views tend to have a smaller intention to perform external whistleblowing. There is a difference between a high professional commitment and a low professional commitment towards intention to perform external whistleblowing. Where the intention of participants to perform external whistleblowing is higher in fraud cases with a high professional commitment